2015
DOI: 10.1111/nph.13281
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal networks and coexistence in species‐rich orchid communities

Abstract: SummaryMultispecies assemblages often consist of a complex network of interactions. Describing the architecture of these networks is a first step in understanding the stability and persistence of these species-rich communities. Whereas a large body of research has been devoted to the description of above-ground interactions, much less attention has been paid to below-ground interactions, probably because of difficulties to adequately assess the nature and diversity of interactions occurring below the ground.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 54 publications
11
102
0
1
Order By: Relevance
“…Members of the Thelephoraceae were also detected in the forest orchid Neottia ovata 1333. However, recent investigations of a large number of terrestrial orchids in Mediterranean grasslands showed that associations with ectomycorrhizal fungi are not restricted to woodland orchids and that grassland orchids may also commonly associate with members of the Thelephoraceae36. Our results are clearly in line with these observations and suggest that these fungi may play a role in the life cycle of grassland orchids as well.…”
Section: Discussionsupporting
confidence: 90%
“…Members of the Thelephoraceae were also detected in the forest orchid Neottia ovata 1333. However, recent investigations of a large number of terrestrial orchids in Mediterranean grasslands showed that associations with ectomycorrhizal fungi are not restricted to woodland orchids and that grassland orchids may also commonly associate with members of the Thelephoraceae36. Our results are clearly in line with these observations and suggest that these fungi may play a role in the life cycle of grassland orchids as well.…”
Section: Discussionsupporting
confidence: 90%
“…2012; Jacquemyn et al. 2015). While mutualistic plant–pollinator networks generally display a nested structure, which minimizes interspecific competition and enhances diversity (Bastolla et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jacquemyn et al. (2015) observed a high degree of specialization and modularity between orchids and their associated orchid mycorrhizal fungi. By contrast, network analysis of arbuscular mycorrhizal (AM) fungal communities showed significant nestedness (Chagnon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Using species delineation based on 3% ITS divergence is unlikely to have masked cryptic Tulasnellaceae species: first, this is a usual threshold and ITS species delineation is validated in Tulasnellaceae by the fact that it is congruent with other genes (Linde, Phillips, Crisp, & Peakall, 2014); second, lowering the threshold to 1.5% did not change OTU delineation in our work. This fungus family is common in several Ophrys species (Jacquemyn, Brys, Waud, Busschaert, & Lievens, 2015; Pecoraro, Girlanda, Liu, Huang, & Perotto, 2015). Only a small difference in mycorrhizal partners was found earlier in closely related species of the genus Orchis in sympatry (Jacquemyn et al., 2011), and sexually deceptive orchids of the genus Chiloglottis were shown to share a narrow taxonomic group of Tulasnella fungi (Roche et al., 2010).…”
Section: Discussionmentioning
confidence: 99%